The early elasmobranch Phoebodus: phylogenetic relationships, ecomorphology and a new time-scale for shark evolution. Issue 1912 (9th October 2019) - Frey, Linda; Coates, Michael; Ginter, Michał; Hairapetian, Vachik; Rücklin, Martin; Jerjen, Iwan; Klug, Christian
Abstract : Anatomical knowledge of early chondrichthyans and estimates of their phylogeny are improving, but many taxa are still known only from microremains. The nearly cosmopolitan and regionally abundant Devonian genus Phoebodus has long been known solely from isolated teeth and fin spines. Here, we report the first skeletal remains of Phoebodus from the Famennian (Late Devonian) of the Maïder region of Morocco, revealing an anguilliform body, specialized braincase, hyoid arch, elongate jaws and rostrum, complementing its characteristic dentition and ctenacanth fin spines preceding both dorsal fins. Several of these features corroborate a likely close relationship with the Carboniferous species Thrinacodus gracia, and phylogenetic analysis places both taxa securely as members of the elasmobranch stem lineage. Identified as such, phoebodont teeth provide a plausible marker for range extension of the elasmobranchs into the Middle Devonian, thus providing a new minimum date for the origin of the chondrichthyan crown-group. Among pre-Carboniferous jawed vertebrates, the anguilliform body shape of Phoebodus is unprecedented, and its specialized anatomy is, in several respects, most easily compared with the modern frilled shark Chlamydoselachus . These results add greatly to the morphological, and by implication ecological, disparity of the earliest elasmobranchs.